Deep exploration of Jiaodong type gold deposit, taking Shanhou gold deposit, southern part of Zhaoping fault as an example - Xu, Zhi-He; Ding, Zheng-Jiang; Gu, Guan-Wen; Jiang, Ji-Yi; Wang, Li; Niu, Xing-Guo (Frontiers in Earth Science, 2022)
Crustal response induced by the subduction of Paleo-Pacific Plate, is crucial to study the metallogenic law and prediction of Jiaodong type gold deposit. Gold deposits are preferentially hosted in the lithospheric-scale second-order faults, which provide migration channels, mineralization corridors, and the physicochemical conditions. Super-large gold deposits in northwestern Jiaobei Terrane are generally controlled by regional linear faults, such as Sansandao, Jiaojia, Zhaoping and Qixia faults. However, Zhaoping fault is exposed sporadically (in Xiadian and Jiangjiayao gold deposits) beneath a thick cover of Quaternary basalts, which indicating that limited information can be obtained by traditional geological survey. In this study, high-precision geophysical surveys such as gravity and controlled source audio frequency magnetotellurics (CSAMT) are conducted in the Shanhou gold deposit, which hosted in southern part of Zhaoping fault. Three integrated geophysical profiles results further identified the spatial distribution of second-order oblique-slip faults of Zhaoping fault and established the relationships between brittle deformation and mineralization. The spatial variability of stratum (high density 2.82 g/cm3 and intermediate to high specific resistivity 4000 Ω m), brittle-slip faults (intermediate density 2.73 g/cm3 and low specific resistivity 200 Ω m) and magmatite (low density 2.57 g/cm3 high specific resistivity 8000 Ω m) are identified by two inversion techniques, including the man-machine interactive inversion technology and nonlinear conjugate gradient technology. In addition, the geophysical inversion pseudo sections delicately portray a smooth-out waveform low specific resistivity anomaly, which strongly couples with the spatial ore-hosted locations and enrichment places. The gold mineralized alteration zones generally dips to southeast and the angle changing from 45° to 30°, which are strong coupling with the large-scale acid magmatic intrusion and extensional tectonics occurred in the late Mesozoic. Finally, according to the deep prospecting prediction, a gold ore body with 10 m in thickness was revealed by drilling below the depth of 1,015 m, which is hosting in the brittle deformation of Zhaoping fracture zone.